Current Advances in Molecular Basis and Mechanisms Regulating Leaf Morphology in Rice - Xu, Peizhou; Ali, Asif; Han, Baolin; Wu, Xianjun (Frontiers in Plant Science, 2018)
Yield is majorly affected by photosynthetic efficiency. Leaves are essential structure for photosynthesis and their morphology especially size and shape in a plant canopy can affect the rate of transpiration, carbon fixation and photosynthesis. Leaf rolling and size are considered key agronomic traits in plant architecture that can subsidize yield parameters. In last era, a number of genes controlling leaf morphology have been molecularly characterized. Despite of several findings, our understanding toward molecular mechanism of leaf rolling and size are under-developed. Here, we proposed a model to apprehend the physiological basis of different genes organized in a complex fashion and govern the final phenotype of leaf morphology. According to this leaf rolling is mainly controlled by regulation of bulliform cells by SRL1, ROC5, OsRRK1, SLL2, CLD1, OsZHD1/2, and NRL1, structure and processes of sclerenchyma cells by SLL1 and SRL2, leaf polarity by ADL1, RFS and cuticle formation by CFL1, and CLD1. Many of above mentioned and several other genes interact in a complex manner in order to sustain cellular integrity and homeostasis for optimum leaf rolling. While, leaf size is synchronized by multifarious interaction of PLA1, PLA2, OsGASR1, and OsEXPA8 in cell division, NAL1, NAL9, NRL1, NRL2 in regulation of number of veins, OsCOW1, OsPIN1, OsARF19, OsOFP2, D1 and GID in regulation of phytohormones and HDT702 in epigenetic aspects. In this review, we curtailed recent advances engrossing regulation and functions of those genes that directly or indirectly can distress leaf rolling or size by encoding different types of proteins and genic expression. Moreover, this effort could be used further to develop comprehensive learning and directing our molecular breeding of rice.